A direct synthesis of platinum/nickel co-catalysts on titanium dioxide nanotube surface from hydrometallurgical-type process streams. (10th November 2018) - Yliniemi, Kirsi; Nguyen, Nhat Truong; Mohajernia, Shiva; Liu, Ning; Wilson, Benjamin P.; Schmuki, Patrik; Lundström, Mari
Abstract: Solutions that simulate hydrometallurgical base metal process streams with high nickel (Ni) and minor platinum (Pt) concentrations were used to create Pt/Ni nanoparticles on TiO2 nanotube surfaces. For this, electrochemical deposition – redox replacement (EDRR) was used that also allowed to control the nanoparticle size, density and Pt/Ni content of the deposited nanoparticles. The Pt/Ni nanoparticle decorated titanium dioxide nanotubes (TiO2 nanotubes) become strongly activated for photocatalytic hydrogen (H2 ) evolution. Moreover, EDRR facilitates nanoparticle formation without the need for any additional chemicals and is more effective than electrodeposition alone. Actually, a 10, 000-time enrichment level of Pt took place on the TiO2 surface when compared to Pt content in the solution with the EDRR method. The results show that hydrometallurgical streams offer great potential as an alternative raw material source for industrial catalyst production when coupled with redox replacement electrochemistry. Graphical abstract: Image 1 Highlights: Production of co-catalytic Pt/Ni surfaces from industrial side-stream solutions. EDRR method has a potential to create catalytic surfaces from process streams. Resultant Pt/Ni surfaces show enhanced photocatalytic H2 evolution cf. TiO2 -NT. EDRR offers a route to utilise also minor components present in process streams. Potential for Circular Economy based industrial nanoparticle manufacture.